2011
DOI: 10.1088/1748-9326/6/3/035103
|View full text |Cite
|
Sign up to set email alerts
|

Infrasound and low frequency noise from wind turbines: exposure and health effects

Abstract: Wind turbines emit low frequency noise (LFN) and large turbines generally generate more LFN than small turbines. The dominant source of LFN is the interaction between incoming turbulence and the blades. Measurements suggest that indoor levels of LFN in dwellings typically are within recommended guideline values, provided that the outdoor level does not exceed corresponding guidelines for facade exposure. Three cross-sectional questionnaire studies show that annoyance from wind turbine noise is related to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 40 publications
1
60
0
1
Order By: Relevance
“…Bolin et al [108] calculated and compared wind turbine and road traffic sound over a broad frequency range (0-2000 Hz) at sound levels considered acceptable in planning guidelines (40 dB L Aeq for wind turbine sound and 55 dB L Aeq for road traffic sound). Compared to road traffic sound, wind turbine sound had lower levels at low frequencies.…”
Section: Audibility Of Infrasound and Low-frequency Soundmentioning
confidence: 99%
“…Bolin et al [108] calculated and compared wind turbine and road traffic sound over a broad frequency range (0-2000 Hz) at sound levels considered acceptable in planning guidelines (40 dB L Aeq for wind turbine sound and 55 dB L Aeq for road traffic sound). Compared to road traffic sound, wind turbine sound had lower levels at low frequencies.…”
Section: Audibility Of Infrasound and Low-frequency Soundmentioning
confidence: 99%
“…However, it was not clear how this conclusion might have been altered had they considered the additional available information regarding LFN and infrasound from wind turbines described elsewhere in this review [i.e., (7,11,22,37,38)]. …”
Section: Review Articles Editorials and Social Commentariesmentioning
confidence: 96%
“…It should be noted that, as discussed in the "Low-Frequency Noise and Infrasound" section of this review, there were a number of studies that specifically addressed the concerns of LFN and infrasound from wind turbines that suggested that these were unlikely to be causative agents in health effects of those living near wind turbines [e.g., (7,11,22,37,38)]. Unfortunately, none of these studies were included as part of the Farboud et al review.…”
Section: Review Articles Editorials and Social Commentariesmentioning
confidence: 99%
“…-Bakker [11] Another source of bias was that three of the studies were reviews of previous literature [6,12,17].…”
Section: Risk Of Bias Across Studiesmentioning
confidence: 99%